Kepuasan Kerja Karyawan Ditinjau dari Persepsi Karyawan Terhadap Negative Expressed Emotion Pimpinan - Meirizki Indah Wulan Ningrum; Sus Budiharto (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2009)
This reseach was aimed to examine the relation between employee's perceptions on leaders' negative expresssed emotion and work satisfaction. The hypothesis was the more negative employee's perception on leader's expresssed emotion, the lower work satisfaction would be and vice versa. The respondents in this reseach were government officials in Yogyakarta. Data collected using questionaires then analyzed by Spearman Rho technique. The results support the reseach hypothesis which the more positive employee's perception on leader's expresssed emotion, the higher employee's work satisfaction and vice versa (R = -0,227 p = 0,039).Keywords: perception on negative expressed emotion of leader, Job satisfaction